1988
DOI: 10.1203/00006450-198809000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Adenine Nucleotide Catabolism in the Human Trophoblast Early and Late in Gestation

Abstract: ABSTRACT. Trophoblastic cells were separated and cul-culture, perfusion, and serial samples of newly delivered, unpertured from human first trimester and term placentae for fused placental tissue. During hypoxia placental anaerobic glystudies on energy metabolism. Changes in the catabolism colysis is activated, as evidenced by increased uptake and conof prelabeled adenine nucleotides and the adenylate energy sumption of glucose and production of lactate (2,4,(7)(8)(9)(10)(11)(12). Stores charge (EC) were follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…West (12) has demonstrated that trophoblast from a mutant mouse with a defect in the glycolytic pathway can survive in the uterus as a anembryonic pregnancy. Trophoblast cells increase susceptibility to hypoxia and energy deprivation with gestationai age (13). These findings suggest that the mitochondrial oxidative phosphorylation in the trophoblast cells is the major source of energy supporting the placental functions.…”
Section: Resultsmentioning
confidence: 97%
“…West (12) has demonstrated that trophoblast from a mutant mouse with a defect in the glycolytic pathway can survive in the uterus as a anembryonic pregnancy. Trophoblast cells increase susceptibility to hypoxia and energy deprivation with gestationai age (13). These findings suggest that the mitochondrial oxidative phosphorylation in the trophoblast cells is the major source of energy supporting the placental functions.…”
Section: Resultsmentioning
confidence: 97%
“…In the human trophoblast, the deamination of AMP to IMP has been shown to dominate over its déphosphoryla tion to adenosine [Vettenranta and Raivio, 1988b], Clearly, the role of this tightly regu lated enzyme [van den Berghe et al, 1977] in the fetoplacental tissues thus cannot be eval uated by in vitro enzymological studies alone, but studies on intact cells containing physiological concentrations of all the effec tors are also required.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the path ways of purine nucleotide metabolism in hu man fetal tissues must be further evaluated in vitro using intact cultured cells, as we have done with the trophoblast [Vettenranta, 1988;Vettenranta and Raivio, 1988b], and/or perfusion of the fetal liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation